1985
DOI: 10.2172/59793
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogic summary of Yucca Mountain, Nevada

Abstract: Quantitative x-ray powder diffraction analysis of tuffs and silicic lavas, using matrix-flushing techniques, has been used to obtain a model of three-dimensional mineral distributions at Yucca Mountain, Nevada. This method of analysis is especially useful in tuff, where the most abundant phases are commonly too fine grained for optical determination. The three-dimensional distributions of primary glass and of tridymite are particularly well constrained. Vitric nonwelded glasses occur above and below the welded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(72 citation statements)
references
References 18 publications
0
72
0
Order By: Relevance
“…As reported by Bish and Vaniman (1985), none of the previous reports of erionite in Yucca Mountain rocks has been verified. However, Bish and Vaniman reported that one sample of erionite has been conclusively identified in a fracture from uE-25a#1 at 1296 ft (395 m).…”
Section: Erion Itementioning
confidence: 69%
See 1 more Smart Citation
“…As reported by Bish and Vaniman (1985), none of the previous reports of erionite in Yucca Mountain rocks has been verified. However, Bish and Vaniman reported that one sample of erionite has been conclusively identified in a fracture from uE-25a#1 at 1296 ft (395 m).…”
Section: Erion Itementioning
confidence: 69%
“…Los Alamos National Laboratory staff have worked to characterize and to understand the mineralogy and petrology of the rocks at and surrounding Yucca Mountain (Heiken and Bevier 1979;Sykes et al 1979;Bish 1981;Bish et al 1981;Caporuscio et al 1982;Vaniman et al 1984;Bish and Vaniman 1985). Bish and Chipera (1989) is the most complete and recent summary of the mineralogy of Yucca Mountain rocks obtained through quantitative X-ray powder diffraction analyses of drill core and cuttings.…”
Section: Introductionmentioning
confidence: 99%
“…Using XRD, we have, however, recently identified erionite as a fracture-lining mineral in UE-25A#1-1296 (395.0 m) (Bish and Vaniman 1985).…”
Section: Fig 4 Graphical Representation Of the Data Inmentioning
confidence: 94%
“…Equation (6) may be used with porosity data for unit Tsw1 to compare calculated compressive strengths with those actually measured. Data in Bish and Vaniman (1985) has been analyzed to provide the following clay contents: 0.071 ± 0.040 in USW G-2 and 0.004 ± 0.005 in USW GU-3 (Note that a standard deviation greater than a mean value is indicative of a non-normal distribution of data). In addition, the average clay content of unit TSwl is 0.039 ± 0.041, based on x-ray analyses of samples from USW G-2, USW GU-3, and USW G-4.…”
Section: Sample Size Effects Experimental Data For Other Rockmentioning
confidence: 99%
“…Data in Bish and Vaniman (1985) indicate that the clay content of unit Tsw2 is 1.9~ ± 3.4~, based on X-ray analyses of samples from usw G-2, USW GU-3, and USW G-4. The clay is not uniformly distributed, being much more prevalent in USW G-2.…”
Section: Thirty-four Samples Obtained From Outcrop Materials Of Unit Tmentioning
confidence: 99%